Combined effect of compression ratio and diethyl ether (DEE) port injection on performance and emission characteristics of a DI diesel engine fueled with upgraded biogas (UBG)-biodiesel dual fuel. (1st December 2017) - Barik, Debabrata; Murugan, S.; Samal, Susmita; Sivaram, N.M.
Highlights: LPG, LNG, and CNG crises can be eliminated by the use of upgraded biogas (UBG). Possibility of running the diesel engine with UBG. BTE increases with increase in compression ratio. UBG-KME-DEE injection improves the efficiency and reduces the emission. With a minor modification UBG can be used in CNG and LNG operated engines. Abstract: In this present investigation, a single cylinder, four stroke, direct injection (DI) diesel engine was modified to operate on dual fuel mode with upgraded biogas (UBG)-Karanja methyl ester (KME). In dual fuel mode, diethyl ether (DEE) was injected as an ignition improver through the air intake manifold of the engine to initiate early combustion of biogas in the combustion chamber. During UBG-KME-DEE operation the compression ratio (CR) of the engine was varied from 16.5 to 18.5 in steps of 1. During investigation, the engine load was varied from 0% to 100% in steps of 25. The DEE injection quantity and the KME injection timing was kept constant at 6% (vol%) and 24.5 °CA bTDC (found to be optimum from previous study by the authors) respectively. The results indicated that UBG-KME-DEE operation with CR 18.5 gave optimum result than those of other CRs. For UBG-KME-DEE-CR18.5 the BTE increased and BSFC decreased by about 7% and 2.2% respectively, than that of KME. A reduction in the specific CO, specific HC, and smoke emissions of 42.2%, 39.5%, and 42.8% was observed for UBG-KME-DEE-CR18.5 in comparison to diesel at full load respectively. However, the specific NO emission for UBG-KME-DEE-CR18.5 was 7.6% higher than that of diesel, but it was 1.2% lower than that of KME, at full load.